New species of the genus Hedysarum L. (Fabaceae) in Mongolia - Bayarmaa Chuluunbat; Nyambayar Batbayar (Mongolian Journal of Biological Sciences)
The family Fabaceae, one of the largest angiosperm families globally, encompasses diverse ecosystems worldwide, notably in Mongolia where it stands as the second largest family. Within this family, Hedysarum L. emerges as the largest genus in the Hedysareae tribe, exhibiting adaptability across Eurasia's temperate zones. Our study marks the first recorded occurrence of Hedysarum tarbagataicum in Mongolia. Field surveys conducted in the Jargalant Khairkhan Mountain revealed its presence, enriching our understanding through detailed observations, photographs, and specimen collection. This species thrives in arid habitats, notably dry stream beds and stony slopes, often coexisting with various flora. Distinguishing characteristics, like drooping flowers and smooth beans, differentiate it from closely related species. Our findings significantly extend the geographical range of H.tarbagataicum, underscoring its rarity and hinting at potential expansions in Central Asia. However, conclusive assertions demand further floristic exploration in the region. This discovery underscores the significance of continued research and specimen collection for a comprehensive understanding of this species' distribution.